Accurate and Strict Identification of Probiotic Species Based on Coverage of Whole-Metagenome Shotgun Sequencing Data - Seol, Donghyeok; Jhang, So Yun; Kim, Hyaekang; Kim, Se-Young; Kwak, Hyo-Sun; Kim, Soon Han; Lee, Woojung; Park, Sewook; Kim, Heebal; Cho, Seoae; Kwak, Woori (Frontiers in Microbiology, 2019)
Identifying the microbes present in probiotic products is an important issue in product quality control and public health. The most common methods used to identify genera containing species that produce lactic acid are matrix-assisted laser desorption/ionization–time of flight mass spectrometry (MALDI-TOF MS) and 16S rRNA sequence analysis. However, the high cost of operation, difficulty distinguishing similar species, and limitations of the current sequencing technologies have made it difficult to obtain accurate results using these tools. To overcome these problems, a whole-genome shotgun sequencing approach has been developed along with various metagenomic classification tools. Widely used tools include the marker gene and k-mer methods, but their inevitable false-positives (FPs) hampered accurate analysis. Therefore, we designed a coverage-based pipeline to reduce the FP problem and achieve more reliable identification of species. The coverage-based pipeline described here not only showed higher accuracy for the detection of species and proportion analysis based on mapping depth, but could be applied regardless of sequencing platform. We believe that the coverage-based pipeline described in this study can provide appropriate support for probiotic quality control, addressing current labeling issues.